Clinical efficacy of simethicone combined with bifidobacterium in the treatment of pediatric aerophagia - He, Ping; Hu, Fangqi; Wang, Le (Frontiers in Pediatrics, 2025)
BackgroundThe causes of children aerophagia are complex, and the treatment methods are diverse. Moreover, it is prone to recurrent attacks. Simethicone oil, as a safe and new type of drug, can be used for treatment.To evaluate the clinical efficacy of simethicone combined with bifidobacterium for the treatment of pediatric aerophagia.MethodsThis study evaluated two treatment approaches for aerophagia. The control group received monotherapy with Bifidobacterium, while the treatment group received combination therapy with Bifidobacterium and simethicone. Clinical efficacy, gastrointestinal symptom scores (GSRS), gastric motility parameters, and adverse events were compared between the two groups.ResultsAmong the 80 children with aerophagia, 14 (17.5%) were preschool children, 56 (70%) were school-aged children and 10 (12.5%) were adolescents children. Seventy children (87.5%) had abdominal distension as their chief complaint. The treatment group exhibited a significantly higher clinical efficacy rate (92.5% vs. 75%, P < 0.05) and lower post-treatment GSRS scores (P < 0.05). Gastric emptying rates at 60 and 120 min were also significantly improved in the treatment group (P < 0.05), although no significant differences were observed in the serum gastrin or plasma motilin levels (P > 0.05).The rate of adverse events was 7.5% in the treatment group and 15% in the control group, with no statistically significant difference (P > 0.05).ConclusionThe combination of simethicone and bifidobacterium enhances gastric emptying, alleviates the clinical symptoms of pediatric aerophagia, and demonstrates favorable safety and tolerability, thereby supporting its clinical application.